In Search of Leading Indicators in Education - Supovitz, Jonathan; Foley, Ellen; Mishook, Jacob (Education Policy Analysis Archives, 2012)
Data have long been considered a key factor in organizational decision-making (Simon, 1955; Lindblom & Cohen, 1979). Data offer perspective, guidance, and insights that inform policy and practice (Newell & Simon, 1972; Kennedy, 1984). Recently, education policymakers have invested in the use of data for organizational improvement in states and districts with such initiatives as Race to The Top (United States Department of Education, 2010) and the development of statewide longitudinal data systems (Institute for Education Sciences, 2010). These and other initiatives focus attention on how data can be used to foster learning and improvement. In other fields, including economics and business, much work has been done to identify leading indicators that predict organizational outcomes. In this paper, we conceptualize how leading indicators might be used in education, using examples from a small sample of school districts with reputations as strong users of data. We define leading indicators as systematically collected data on an activity or condition that is related to a subsequent and valued outcome, as well as the processes surrounding the investigation of those data and the associated responses. Identifying leading indicators often prompts improvements in a district’s system of supports. To develop this concept, we describe four examples of how districts identified and used key indicators to anticipate learning problems and improve student outcomes. We also describe the infrastructure and other supports that districts need to sustain this ambitious form of data use. We conclude by discussing how leading indicators can bring about more intelligent use of data in education.